Enhanced Biomechanical Stability in Proximal Humeral Fractures: Finite Element Analysis of a Novel Endosteal Anatomical Support Nail for Improved Fixation in Elderly Patients - Jiawen Chen; Zhonghe Wang; Changda Li; Peiyu He; Zhongxuan Chen; Lijun Sun; Xiaoyan Cao; Na Tian; Xiang Dong; Peifu Tang; Hua Chen (Orthopaedic Surgery)
ABSTRACT Objectives Intramedullary nailing is preferred for treating elderly proximal humeral fractures, but secondary reductions are common, particularly in elderly and osteoporotic patients. This occurs due to the intramedullary nail fixation's insufficient anti‐varus and anti‐rotational capacities and high stress at the bone–implant interface. We aim to enhance the anti‐varus and anti‐rotational stability of the fixation structure while reducing the stresses on the bone and internal fixation through structural design. Materials and Methods We developed a novel endosteal anatomical support nail (EASN) that integrates an endosteal torus construct into the proximal portion of the angle‐stable proximal humerus nail. The endosteal torus construct includes endosteal anatomical support (EAS) with a flat plane that allows direct fixation of the humeral head fragments and is shaped to conform to the medial side of the medullary cavity of the proximal humerus. We conducted finite element analysis to assess the biomechanical stability of four constructs: EAS with a calcar screw (CS), EAS without CS, non‐EAS with CS, and non‐EAS without CS. This analysis determined the contribution of the EAS to the mechanical stability of the proximal humerus in two‐part PHF with medial column disruption. Specimens were subjected to loads simulating partial‐weight‐bearing (as in rising from a chair or using crutches) and full‐weight‐bearing (as in rising from bed). We evaluated the stiffness of the construct, displacement at the fracture site, von Mises stress, and stress distribution. Results Under compressive or rotational loads, the EAS construct, with or without CS, was significantly stiffer than the non‐EAS construct. Displacement at the fracture site was significantly less with the EAS fixation than with the non‐EAS fixation. However, the stiffness and displacement at the fracture site of the EAS fixation without CS were comparable to those of the non‐EAS construct with CS. The EAS construct reduced the load on the nail and decreased the risk of implant failure. Both von Mises stress and stress distribution were significantly lower following fixation with the EAS constructs. Conclusions This study introduces a novel EAS concept to enhance the anti‐varus and anti‐rotational capabilities of the humeral head and distribute stress at the bone–implant interface in treating elderly PHFs. This strategy shows promise based on our limited analysis.